An antisense oligodeoxynucleotide targeted against the type II beta regulatory subunit mRNA of protein kinase inhibits cAMP-induced differentiation in HL-60 leukemia cells without affecting phorbol ester effects. - Tortora, G (1990)
The type II beta regulatory subunit of cAMP-dependent protein kinase (RII beta) has been hypothesized to play an important role in the growth inhibition and differentiation induced by site-selective cAMP analogs in human cancer cells, but direct proof of this function has been lacking. To address this issue, HL-60 human promyelocytic leukemia cells were exposed to RII beta antisense synthetic oligodeoxynucleotide, and the effects on cAMP-induced growth regulation were examined. Exposure of these cells to RII beta antisense oligodeoxynucleotide resulted in a decrease in cAMP analog-induced growth inhibition and differentiation without apparent effect on differentiation induced by phorbol esters. This loss in cAMP growth regulatory function correlated with a decrease in basal and induced levels of RII beta protein. Exposure to RII beta sense, RI alpha and RII alpha antisense, or irrelevant oligodeoxynucleotides had no such effect. These results show that the RII beta regulatory subunit of protein kinase plays a critical role in the cAMP-induced growth regulation of HL-60 leukemia cells.